Tuning the Catalytic Water Oxidation Activity through Structural Modifications of High-Nuclearity Mn-oxo Clusters [Mn18M] (M = Sr2+, Mn2+) - Schmitt, Wolfgang (My University, 2021)
The water oxidation half-reaction is considered the bottleneck in the development of technological advances to replace fossil fuels with sustainable and economically affordable energy sources. In natural photosynthesis, water oxidation occurs in the oxygen evolving complex (OEC), a manganese-oxo cluster {Mn4CaO5} with a cubane-like topology that is embedded within a redox-active protein environment located in photosystem II (PS II). Therefore, the preparation of biomimetic manganese-based compounds is appealing for the development of efficient and inexpensive water oxidation catalysts. Here, we present the water oxidation catalytic activity of a high-nuclearity mixed-metal manganese-strontium cluster, [MnIII12MnII6Sr(μ4-O8)(μ3-Cl)8(HLMe)12(MeCN)6]Cl2∙15MeOH (Mn18Sr) (HLMe = 2,6-bis(hydroxymethyl)-p-cresol), in neutral media. This biomimetic mixed-valence cluster features different cubane-like motifs and it is stabilized by redox-active, quinone-like organic ligands. The complex displays a low onset overpotential of 192 mV and overpotentials of 284 and 550 mV at current densities of 1 mA cm−2 and 10 mA cm−2, respectively. Direct O2 evolution measurements under visible light-driven water oxidation conditions demonstrate the catalytic capabilities of this cluster, which exhibits a turnover frequency of 0.48 s−1 and a turnover number of 21.6. This result allows for a direct comparison to be made with the structurally analogous Mn-oxo cluster [MnIII12MnII7(µ4-O)8(µ3-OCH3)2(µ3-Br)6(HLMe)12(MeOH)5(MeCN)]Br2·9MeCN·MeOH (Mn19), the water oxidation catalytic activity of which was recently reported by us. This work highlights the potential of this series of compounds towards the water oxidation reaction and their amenability to induce structural changes that modify their reactivity. View Full-Text
Keywords: Immobilized molecular catalyst; Biomimetic catalyst; Cubane-type structure; Redox-active ligands; Manganese; Water oxidation catalysis; Oxygen evolution reaction